Natural Variation of Lignocellulosic Components in Miscanthus Biomass in China - Xu, Pingping; Cheng, Senan; Han, Yanbin; Zhao, Dongbo; Li, Hongfei; Wang, Yancui; Zhang, Guobin; Chen, Cuixia (Frontiers in Chemistry, 2020)
Lignocellulose content is an important factor affecting the conversion efficiency of biomass energy plants. In this study, 179 Miscanthus accessions in China were used to determine the content of lignocellulose components in stems via acid hydrolysis and high-performance liquid chromatography. Results showed that the average lignocellulose content of wild Miscanthus germplasm resources was 80.27% ± 6.51%, and the average content of cellulose, hemicellulose, lignin, extracts, and total ash was 38.38% ± 3.52%, 24.23% ± 4.21%, 17.66% ± 1.56%, 14.50% ± 5.60%, and 2.53% ± 0.59%, respectively. The average lignocellulose content of M. sinensis, M. ﬂoridulus, M. nudipes, M. sacchariﬂorus, M. lutarioriparius, and the hybrids was 77.94% ± 6.06%, 75.16% ± 4.98%, 75.68% ± 3.02%, 83.71% ± 4.78%, 81.50% ± 5.23%, and 74.72% ± 7.13%, respectively. In all the tested materials, the highest cellulose content was 48.52%, and the lowest was 29.79%. Hemicellulose had the maximum content of 34.23% and a minimum content of 15.71%. The highest lignin content was 23.75%, and the lowest was 13.01%. The lignocellulosic components of different ploidy materials were compared. The content of lignocellulosic components of diploid M. sacchariﬂorus was higher than that of tetraploid M. sacchariﬂorus, and the content of lignocellulosic components of diploid M. lutarioriparius was lower than that of tetraploid M. lutarioriparius. Analysis of the relationship between the changes in lignocellulosic components and geographical locations of Miscanthus showed that the holocellulose and hemicellulose content was significantly positive correlated with the latitude of the original growth location. Results indicated that the lignocellulosic components of Miscanthus resources in China are rich in genetic diversity.